The effects of community education on tobacco use among older adults in China - Shuang Yu; Yu Liu; Manyi Wang; Yinhe Liang (Tobacco Induced Diseases)
Introduction Smoking among older adults is increasingly linked to chronic diseases and higher mortality rates. However, the influence of community education on smoking behavior in older adults remains understudied. This research examines the causal effect of community education on smoking habits of older adults in China.